Comparison of fractional and integer order control of an hexapod robot - Silva, Manuel (2003)
This paper studies the dynamics of foot-ground interaction and the performance of integer and fractional order controllers in multi-legged locomotion systems. For that objective the robot precribed motion is characterized in terms of several locomotion variables. Moreover, to compare the system performance, we formulate six performance measures of the walking robot namely, the mean absolute power, the mean power dispersion, the mean power lost in the joint actuators, the mean force of the interface body-legs per walking distance and mean square error of the hip and foot trajectories. A set of model-based experiments reveals the influence of the different controller implemantations in the proposed indices.